2015
DOI: 10.5194/acp-15-6467-2015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of overshooting deep convection on local transport and mixing in the tropical upper troposphere/lower stratosphere (UTLS)

Abstract: Abstract. In this study we examine the simulated downward transport and mixing of stratospheric air into the upper tropical troposphere as observed on a research flight during the SCOUT-O3 campaign in connection with a deep convective system. We use the Advanced Research Weather and Research Forecasting (WRF-ARW) model with a horizontal resolution of 333 m to examine this downward transport. The simulation reproduces the deep convective system, its timing and overshooting altitudes reasonably well compared to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 77 publications
2
56
0
Order By: Relevance
“…Extratropical STT events most commonly occur during synopticscale tropopause folds Tang and Prather, 2012;Frey et al, 2015) and are characterised by tongues of high potential vorticity (PV) air descending to lower altitudes. As these tongues become elongated, filaments disperse away from the tongue and mix irreversibly into the troposphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extratropical STT events most commonly occur during synopticscale tropopause folds Tang and Prather, 2012;Frey et al, 2015) and are characterised by tongues of high potential vorticity (PV) air descending to lower altitudes. As these tongues become elongated, filaments disperse away from the tongue and mix irreversibly into the troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…As these tongues become elongated, filaments disperse away from the tongue and mix irreversibly into the troposphere. STT can also be induced by deep overshooting convection (Frey et al, 2015), tropical cyclones (Das et al, 2016), and mid-latitude synoptic-scale disturbances (e.g. Stohl et al, 2003;Mihalikova et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Vigorous turrets associated with deep convection generate intense precipitation that influences the hydrological cycle and large anvil shields that modulate radiation due to their extensive spatial and temporal coverage (Feng et al, 2011;Wang et al, 2015). Overshooting tops associated 15 with strong updrafts are responsible for stratosphere-troposphere exchange (Homeyer et al, 2014;Frey et al, 2015) and can be an indicator of a severity of thunderstorm (Proud, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, uplift in deep convection is the underlying cause, but deep convection is a turbulent process and air entering at the surface would be expected to mix with its surroundings during ascent. Noting that the minimum ozone concentrations observed in the TTL above Darwin were too 25 low to originate in the boundary layer locally, Heyes et al (2009) proposed long-range transport in the TTL from a 'hot-spot' region north-east of New Guinea. Newton et al (2016) found that the minimum concentrations measured over Manus were only consistent with ozone measurements in the lowest 300 m over the island, suggesting uplift of air from near the surface to the TTL with little or no mixing (see below).…”
mentioning
confidence: 99%
“…The TTL lies above the main convective outflow (10-13 km) and although deep convection can reach, and even overshoot the tropopause (e.g. Frey et al, 2015), the region is not well-mixed and both radiative and large-scale dynamical processes influence its structure and composition (Fueglistaler et al, 2009). A key question about the TTL is whether deep convection is nevertheless capable of lifting very short-lived halogenated species near enough to the tropopause that their 5 breakdown products reach the stratosphere and contribute to ozone destruction.…”
mentioning
confidence: 99%